2′‐Fluoro‐6′‐methylene carbocyclic adenosine and its phosphoramidate prodrug: A novel anti‐HBV agent, active against drug‐resistant HBV mutants. Issue 3 (6th February 2018) - Singh, Uma S.; Mulamoottil, Varughese A.; Chu, Chung K.
Abstract: Chronic hepatitis B (CHB) is one of the major causes of morbidity and mortality worldwide. Currently, clinically approved nucleos(t)ide analogs (NAs) are very efficient in reducing the load of hepatitis B virus (HBV) with minimum side effects. However, the long‐term administration of antiviral drugs promotes HBV for potential drug resistance. To overcome this problem, combination therapies are administered, but HBV progressively altered mutations remain a threat. Therefore, optimally designed NAs are urgently needed to treat drug‐resistant HBV. Herein, 2′‐fluoro‐6′‐methylene carbocyclic adenosine (FMCA) and its phosphoramidate (FMCAP) have been discovered, which may be utilized in combination therapies for curing drug‐resistant chronic hepatitis B. In preclinical studies, these carbocyclic NAs demonstrated potential anti‐HBV activity against adefovir, as well as lamivudine (LMV/LAM) drug‐resistant mutants. In vitro, these molecules have demonstrated significant activity against LMV/entecavir (ETV) triple mutants (L180M + S202G + M204V). Also, preliminary studies of FMCA/FMCAP in chimeric mice and female Non‐obese diabetic/severe combined immunodeficiency (NOD/SCID) mouse models having the LMV/ETV triple mutant have shown a high rate of reduction of HBV DNA levels compared to ETV. In this review, we have summarized preclinical studies of FMCA and its phosphoramidate prodrug (FMCAP).